Meningkatkan Minat Belajar Anak Melalui Media Augmented Reality di TK Arjuna Kabupaten Bengkulu Utara - Nurul Marta Havizah; Asnawati Asnawati; Syisva Nurwita (Early Childhood Research and Practice, 2026)
This study examines efforts to enhance children's learning interest through the utilization of augmented reality (AR) media at Arjuna Kindergarten (TK), North Bengkulu Regency. The research was prompted by the children's low learning interest, as evidenced by a lack of attention, enthusiasm, and engagement during the learning process, thereby highlighting the need for engaging and innovative instructional media. The study sought to evaluate the improvement of children's learning interest through the integration of AR media. The methodology employed was Classroom Action Research (CAR), conducted across two cycles, with each cycle consisting of two sessions comprising planning, action, observation, and reflection stages. The research subjects involved 15 children aged 5–6 years. Data were gathered using observation and documentation techniques, while data analysis combined qualitative descriptive and quantitative approaches. The findings demonstrated that the children's learning interest steadily improved in each session. In Cycle I, Session I, the children achieved a percentage score of 29%, falling under the "Beginning to Develop" category, which subsequently rose to 37% (retaining the same category) in Cycle I, Session II. This upward trajectory continued in Cycle II, with scores rising to 51% in Session I, meeting the "Developing as Expected" criteria, and ultimately reaching a significant peak of 87% in Session II, classified as "Highly Well-Developed." In conclusion, the utilization of augmented reality media is highly effective in enhancing children's learning interest at TK Arjuna, North Bengkulu Regency.